CURRENT STATUS OF AVAILABILITY OF SOIL OF POLTAVA REGION WITH BORON - Коваль, В. В.; Наталочка, В. О.; Ткаченко, С. К.; Міненко, О. В. (Scientific Progress & Innovations, 2013)
The results of years of research are shown and the current state of agricultural land fertility in Poltava region are summarized. The dynamics of providing of soils of Poltava region with boron are analyzed and recommendations for their further suspension of degradation and also resumption of fertility. Laboratory studies during 2001-2010, determined that the boron content in soils of the region for the last two surveys essentially unchanged. According to the VIIIth round of survey, the average content of boron is 1.05 mg / kg of soil to 1.11 mg / kg in the IXth round.